Eksploitasi Anak Sebagai Pedagang Asongan ditinjau dari UU Perlindungan Anak pada Masa Pandemi Covid-19 - Cipta PutraI Ketut Wira Cipta Putra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
Legal arrangements for child exploitation during the Covid-19 pandemic have not yet been included in the Criminal Code (KUHP). So that parents who employ their children as hawkers are still free from legal snares and can easily justify economically. This study aims to examine the legal arrangements for perpetrators of criminal acts of child exploitation as hawkers and reveal criminal sanctions for perpetrators of acts of exploitation of children as hawkers during the Covid-19 pandemic. This research method uses normative legal research by applying a conceptual approach and legislation. The data used are primary, secondary and tertiary legal data obtained by the recording method. After the data has been collected, the next step is to process and analyze it in a systematic way with legal intervention. The results of the study show that legal arrangements for perpetrators of criminal acts of exploitation of children during the Covid-19 pandemic, one of which is child exploitation, are not specifically regulated in Article 13 of Law no. 35 of 2014 amendments to Law no. 23 of 2002 concerning Child Protection. Therefore, in this case there is a void of norms, but the crime of child exploitation based on the provisions of Article 103 of the Criminal Code states that crimes against children are a special crime. Related to criminal sanctions, they are sentenced to a maximum imprisonment of ten years or a maximum fine of Rp. 200,000,000.00 (two hundred million rupiah